Fundamentals of premixed turbulent combustion - Lipatnikov, Andrei (Boca Raton, FL : Taylor & Francis, 2013)
'Lean burning of premixed gases is considered to be a promising combustion technology for future clean and highly efficient gas turbine engines. This book highlights the phenomenology of premixed turbulent flames. The text provides experimental data on the general appearance of premixed turbulent flames, physical mechanisms that could affect flame behavior, and physical and numerical models aimed at predicting the key features of premixed turbulent combustion. The author aims to provide a simple introduction to the field for advanced graduate and postgraduate students. Topics covered include Laminar premixed flames, homogenous isotropic turbulence, and incompressible turbulent flow'--
Includes bibliographical references and index.
Keywords: Gas-turbines -- Combustion